OTX2 mutation associated with severe myopia in a Canadian family. (4th May 2022) - Wangding, Snow; Colaiacovo, Samantha; Makar, Inas; Saleh, Maha
ABSTRACT: Purpose: To describe a case of high myopia in a pediatric patient with a mutation in the OTX2 gene and further characterize the diverse ocular phenotypes of heterozygous OTX2 mutations. Patient and Methods: We describe a three-year-old girl who presented at two months old with abnormal eye movements and suspected retinal dystrophy. Clinical exam and electroretinography (ERG) were conducted, and molecular next generation sequencing (NGS) with the Inherited Retinal Dystrophies panel was completed in our patient and offered to the family. Results: Further examination revealed progressive high myopia in our patient and her mother, alongside diffuse retinal thinning and normal ERG. NGS identified a likely pathogenic variant in the OTX2 gene (c.235 G > A) that was maternal in origin. There were no extra-ocular concerns in our patient, and brain MRI was normal. Conclusions: While OTX2 mutations are known to cause retinopathy, this case presents a unique phenotype through a heterozygous missense variant (c.235 G > A) underlying high myopia in a three-generation family. This case further supports the role of OTX2 in ocular development and demonstrates the variable expressivity of OTX2 mutations. Genetic testing in families with high myopia may be useful in future surveillance and preparation for ocular and extra-ocular complications associated with OTX2 -syndrome presentations.